The Red Queen lives: Epistasis between linked resistance loci. (3rd February 2016) - Metzger, César M. J. A.; Luijckx, Pepijn; Bento, Gilberto; Mariadassou, Mahendra; Ebert, Dieter
Abstract : A popular theory explaining the maintenance of genetic recombination (sex) is the Red Queen Theory. This theory revolves around the idea that time‐lagged negative frequency‐dependent selection by parasites favors rare host genotypes generated through recombination. Although the Red Queen has been studied for decades, one of its key assumptions has remained unsupported. The signature host‐parasite specificity underlying the Red Queen, where infection depends on a match between host and parasite genotypes, relies on epistasis between linked resistance loci for which no empirical evidence exists. We performed 13 genetic crosses and tested over 7000 Daphnia magna genotypes for resistance to two strains of the bacterial pathogen Pasteuria ramosa . Results reveal the presence of strong epistasis between three closely linked resistance loci. One locus masks the expression of the other two, while these two interact to produce a single resistance phenotype. Changing a single allele on one of these interacting loci can reverse resistance against the tested parasites. Such a genetic mechanism is consistent with host and parasite specificity assumed by the Red Queen Theory. These results thus provide evidence for a fundamental assumption of this theory and provide a genetic basis for understanding the Red Queen dynamics in the Daphnia–Pasteuria system.